Model Matematika Dampak Industri 4.0 terhadap Ketenagakerjaan Menggunakan Pendekatan Sistem - Rio Aurachman (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2019)
The objective of this research was to provide a mathematical model that can explain the relationship between the unemployment rate, openness to technology, and people development initiatives to overcome technology development. These research discussions were carried out in the context of predicted technological developments related to Industry 4.0 which caused the loss of several jobs and formed new business models that will provide new jobs. The method used is to using system approach so that mathematical modeling can be obtained from Influence Diagrams which have been designed in previous research. Mathematical models illustrate that openness to technology is directly proportional to the number of unemployed. And the unemployment rate is inversely proportional to the level of human resource development. Development of human resources that are too large without being carried out with openness and technological progress, can also cause unemployment. This mathematical model can be used as a decision maker to understand and establish appropriate policies in the face of this Industry 4.0 change.